Nonlinear Analysis of the Hermetic Postament Safety During Technology Accident in the Nuclear Power Plant - Králik Juraj (Transactions of the VŠB: Technical University of Ostrava, Civil Engineering Series, 2017)
This paper describes the nonlinear analysis of the nuclear power plant (NPP) postament safety under a high internal overpressure and temperature. The scenario of the hard accident in NPP and the methodology of the calculation of the safety of the technology segments are presented. The elastoplastic behavior of steel material dependent on temperature was considered in software ANSYS. The safety analysis of the original and upgraded postament structure is described here.